Maternal Labor Supply: Perceived Returns, Constraints, and Social Norms - Teodora Boneva; Katja Maria Kaufmann; Christopher Rauh (Institute of Labor Economics (IZA), 2021)
We design a new survey to elicit quantifiable, interpersonally comparable beliefs about pecuniary and non-pecuniary benefits and costs to maternal labor supply decisions, to study how beliefs vary across and within different groups in the population and to analyze how those beliefs relate to choices. In terms of pecuniary returns, mothers' (and fathers') later-life earnings are perceived to increase the more hours the mother works while her child is young. Similarly, respondents perceive higher non-pecuniary returns to children's cognitive and non-cognitive skills the more hours a mother works and the more time her child spends in childcare. Family outcomes on the other hand, such as the quality of the mother-child relationship and child satisfaction, are perceived to be the highest when the mother works part-time, which is also the option most respondents believe their friends and family would like them to choose. There is a large heterogeneity in the perceived availability of full-time childcare and relaxing constraints could substantially increase maternal labor supply. Importantly, it is perceptions about the non-pecuniary returns to maternal labor supply as well as beliefs about the opinions of friends and family that are found to be strong predictors of maternal labor supply decisions, while beliefs about labor market returns are not.
Keywords: J22; J13; I26; 330; labor supply; childcare; beliefs; child penalties